Digital credit, financial literacy and household indebtedness - Peter Wamalwa; Irene W. Rugiri; Julienne Lauler (Kenya Bankers Association (KBA), 2019)
Easier access to credit has been emphasized to ease financial constraints that impede investments critical for improving earnings and alleviating poverty. This paper analyses the uptake of digital credit and its impact on household indebtedness in Kenya. The empirical results show that financial literacy reduces utilisation of digital credit. However, using conventional credit is preferred to digital credit. The empirical results also show that individuals using digital credit are more likely to sale household assets to repay their loan, have a higher number of loans and lower income compared to those using conventional credit or not using credit.
Keywords: 330; Verbraucherkredit; Private Verschuldung; Finanzwissen; Kenia